Contributions to the knowledge of Thysanoptera (Insecta) from Japan - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2021)
For the Thysanoptera fauna of Japan, Masumoto (2016) listed 405 species in 138 genera and four families, Aeolothripidae, Merothripidae, Thripidae and Phlaeothripidae. However, the species total included several undescribed species, and subsequently further genera and species have been described or recorded. Moreover, recently the present authors have found, through the study of collections in the Laboratory of Entomology, Tokyo University of Agriculture, seven more species of six genera that had previously not been known from Japan.